A Review on the Nomenclature and Taxonomy of the Old World Thread-Legged Bug Genus Pleias (Hemiptera: Reduviidae: Emesinae) - Zhuo Chen; Hu Li; Wanzhi Cai (Insects)
The nomenclatural and taxonomic issues regarding the thread-legged bug genera Pleias Kirkaldy, 1901 and Bagauda Bergroth, 1903 are reviewed, and Pleias is concluded to be the valid name of the genus. A comprehensive review of Pleias is conducted, resulting in 18 new combinations and two new synonymies [P. aelleni (Villiers, 1970) comb. n., P. atypica (Ghate, Boyane & Joshi, 2019) comb. n., P. avida (Bergroth, 1903) comb. n., P. brunnea (McAtee & Malloch, 1926) comb. n., P. cavernicola (Paiva, 1919) comb. n., P. creppei (Lhoste, 1939) comb. n. = Bagauda gilletti Miller, 1956 syn. n., P. ernstmayri (Kulkarni & Ghate, 2016) comb. n., P. furcosa (Ribes, 1987) comb. n., P. gigantea (Lhoste, 1939) comb. n., P. lucifuga (McAtee & Malloch, 1926) comb. n., P. monodi (Villiers, 1972) comb. n., P. similis (Wygodzinsky, 1966) comb. n., P. smithersi (Wygodzinsky, 1966) comb. n., P. splendens (Distant, 1906) comb. n., P. strinatii (Villiers, 1970) comb. n., P. tenebricola (Horváth, 1910) comb. n., P. wagneri (Villiers, 1949) comb. n. = B. eriksoni Miller, 1954 syn. n., and P. zetteli (Rédei, 2005) comb. n.]. The bibliographies, diagnosis, and known distribution records are presented for all described species, and three new species [P. fashengisp. n. (from Yunnan, China), P. serratasp. n. (from Sabah, Malaysia), and P. trimaculatasp. n. (from Sulawesi, Indonesia)] are described. The identification keys to the African and Asian species of Pleias are provided. The systematic relationships, distribution, and ecology of the genus are discussed.